A high first-efficiency silicon oxide-based negative electrode material and preparation method thereof
By covering nanosilver, lithium titanate and carbon layers on the silicon oxide negative electrode material, the problems of high irreversible capacity, low conductivity and large volume changes in silicon oxide negative electrode materials in lithium-ion batteries are solved, and a negative electrode material with high first-term efficiency, low volume effect and high conductivity are achieved, extending the service life of the battery.
Patent Information
- Application Number
- CN202210827877.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-07-14
AI Technical Summary
The silicon oxide negative electrode material has high irreversible capacity, low conductivity and large volume changes during the circulation of lithium-ion batteries, resulting in low efficiency and short battery life for the first time.
Partially lithiated silicon oxide core and nanosilver composite particles were used to coat the lithium titanate layer and carbon layer, and a high-first-effect silicon oxide based anode material was prepared by sol-gel method and chemical vapor deposition method.
It significantly improves the first Coulomb efficiency and cycling performance of the material, reduces volume changes and SEI film generation, and extends the service life of the battery.
Smart Images

Figure HDA0003747186880000011 
Figure HDA0003747186880000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing silicon dioxide composite materials, and in particular to a high-initial-efficiency silicon dioxide-based negative electrode material and a preparation method thereof. Background Art
[0002] Silicon oxide can be used as a lithium-ion negative electrode material and has attracted widespread attention due to its high capacity. At present, with the popularization of electric vehicles, the demand for high-energy-density lithium-ion batteries is growing, and the use of silicon oxide negative electrode materials is also increasing. However, silicon oxide will form a SEI film and a large amount of lithium silicate phase during the first lithium insertion process of the cycle. These substances are irreversible in subsequent cycles, resulting in a large amount of irreversible capacity during the first lithium insertion process, resulting in a low first coulombic efficiency. In addition, the low conductivity of silicon oxide negative electrode materials leads to poor rate performance, which hinders its use in high-rate charge and discharge scenarios. Silicon oxide will also produce a large volume change (~100%) during the cycle process, causing deformation of the pole piece and battery cell, shortening the service life of the battery. Summary of the invention
[0003] Based on the technical problems mentioned in the background technology, such as the large volume effect of silicon oxide materials in the negative electrode of lithium-ion batteries during the electrochemical deintercalation and extraction of lithium, which affects the cycle performance of electrode materials, and the low conductivity and low initial efficiency of such materials, the present invention proposes a silicon oxide-based negative electrode material with high initial efficiency, small volume effect and high conductivity, and a preparation method thereof.
[0004] The invention provides a high first-efficiency silicon oxide-based negative electrode material, comprising a partially lithiated silicon oxide core and composite particles composed of nanosilver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particles, and a carbon layer coated on the surface of the lithium titanate layer.
[0005] The components of the partially lithiated silicon oxide core include silicon oxide and lithium silicate phases.
[0006] Preferably, in the negative electrode material, the average particle size of the silicon oxide core is 1-10 μm, nanosilver accounts for 0.05%-1% of the total mass of the negative electrode material, lithium titanate accounts for 0.3%-5% of the total mass of the negative electrode material, and carbon accounts for 0.5%-3% of the total mass of the negative electrode material.
[0007] A method for preparing a high first-efficiency silicon oxide-based negative electrode material comprises the following steps:
[0008] S1, coating nanosilver on the surface of silicon dioxide particles to obtain particles A;
[0009] S2, coating the lithium titanate precursor on the surface of the particle A by a sol-gel method to obtain a powder B;
[0010] S3. Placing the powder B in a chemical vapor deposition furnace, and performing carbon coating by chemical vapor deposition at high temperature to obtain a high-efficiency silicon dioxide-based negative electrode material.
[0011] Preferably, in S1, the surface of silicon oxide particles is coated with nanosilver by chemical plating, wherein the process includes: firstly sensitizing the surface of silicon oxide with stannous chloride solution, and then adding silver nitrate solution to react and deposit nanosilver.
[0012] Preferably, in S1, the specific steps of coating the surface of silicon dioxide particles with nanosilver by chemical plating include: adding silicon dioxide particles to stannous chloride solution to obtain a mixed solution, heating and stirring the mixed solution for reaction for 0.5 to 3 hours, then adding silver nitrate solution, continuing to heat and stir the mixed solution for reaction for 1 to 3 hours, filtering and drying after the reaction is completed; preferably, in S1, the temperature of the heating and stirring reaction is 30 to 50°C, and the stirring speed is 100 to 300 r / min; preferably, in S1, the concentration of the stannous chloride solution is 0.1 to 1 mol / L; preferably, in S1, the concentration of the silver nitrate solution is 0.1 to 1 mol / L; preferably, in S1, the solid content of the mixed solution is 20% to 60%; preferably, in S1, the drying method is air drying or vacuum drying, and the drying temperature is 30 to 100°C.
[0013] Preferably, in S2, the titanium source solution is mixed with particles A and a chelating agent to obtain a mixed solution, which is then heated and stirred for reaction. After the reaction is completed, a lithium source is added under stirring to form a gel, which is then freeze-dried to obtain powder B; preferably, in S2, the solid content of the mixed solution is 20% to 40%, the molar concentration of the chelating agent in the mixed solution is 0.01 to 1 mol / L, the molar ratio of the titanium source to the lithium source is 1:(1 to 3), and the mass ratio of the lithium source to the particles A is 1:(6 to 25); preferably, in S2, the temperature of the heated and stirred reaction is 40 to 80°C, and the time is 0.5 to 1h; preferably, in S2, the titanium source is at least one of butyl titanate, isopropyl titanate, and ethyl titanate, the lithium source is lithium acetate, and the chelating agent is at least one of polyethyleneimine, triethanolamine, and citric acid; preferably, the titanium source solution is obtained by mixing a titanium source with ethanol.
[0014] Preferably, in S3, the temperature of carbon coating by chemical vapor deposition is 800-1000° C. and the time is 1-5 h.
[0015] Preferably, in S3, the powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at high temperature for carbon coating to obtain a high first-efficiency silicon dioxide-based negative electrode material; preferably, in S3, the gas flow rate of the argon is 50 to 200 ml / min, and the volume ratio of argon to acetylene is 4:1 to 1:4.
[0016] Preferably, in S1, the average particle size of the silicon oxide particles is 1 to 10 μm.
[0017] In a specific preparation process of the present invention, first, highly conductive nanosilver particles are uniformly deposited on the surface of silicon oxide particles. The nanosilver particles present a three-dimensional conductive network effect to improve the conductive properties of the material, and at the same time connect silicon oxide and lithium titanate with low conductivity to stabilize the structure of the material; then, a gel-like lithium titanate precursor is used to uniformly coat the intermediate product, and the composition and particle distribution of the gel are maintained by freeze-drying. The gel-like lithium titanate precursor is in situ converted into lithium-intercalated lithium titanate without expansion by subsequent high-temperature CVD carbon coating. At the same time, in this process, excessive lithium ions in the gel diffuse into the interior of the silicon oxide particles to form a lithium silicate phase, thereby reducing the irreversible capacity during the first lithium insertion process and improving the first efficiency of the material; the formed lithium titanate coating layer not only inhibits the expansion of silicon oxide during the lithium insertion process, but also reduces the lithium ion consumption during the first lithium insertion process due to the small amount of SEI film formed by lithium titanate during the charge and discharge cycle, thereby further improving the first efficiency of the material. In addition, the surface of silicon dioxide@lithium titanate is carbon-coated with acetylene to further improve the conductivity, while reducing the specific surface area of the material, reducing the formation of SEI film, and improving the first coulombic efficiency of the material.
[0018] A lithium ion battery, wherein the negative electrode material of the lithium ion battery comprises the silicon oxide-based negative electrode material.
[0019] The beneficial effects of the present invention are as follows:
[0020] The present invention proposes a high first-efficiency silicon oxide-based negative electrode material, comprising a partially lithiated silicon oxide core and composite particles composed of nanosilver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particles, and a carbon layer coated on the surface of the lithium titanate layer; wherein the core components of the partially lithiated silicon oxide particles include silicon oxide and lithium silicate phases, which can reduce the irreversible capacity during the first lithium insertion process and improve the first efficiency of the material; the nanosilver coated on the surface of the core presents a three-dimensional conductive network effect, which can improve the conductive performance of the material, and at the same time connect the silicon oxide core and the lithium titanate layer with low conductivity to stabilize the structure of the material; the lithium titanate layer not only inhibits the expansion of silicon oxide during the lithium insertion process, but also reduces the lithium ion consumption during the first lithium insertion process due to the small amount of SEI film formed by lithium titanate during the charge and discharge cycle process, further improving the first efficiency of the material; the outermost coated carbon layer can not only further improve the conductivity, but also reduce the specific surface area of the material, reduce the generation of SEI film, and improve the first coulomb efficiency of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the silicon oxide-based negative electrode material prepared in Example 2 of the present invention.
[0022] Figure 2 The electrochemical performance test results of the battery assembled with the silicon oxide-based negative electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is described in detail below through specific embodiments.
[0024] Example 1
[0025] A high first-efficiency silicon oxide-based negative electrode material comprises a partially lithiated silicon oxide core, composite particles composed of nano-silver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particle, and a carbon layer coated on the surface of the lithium titanate layer.
[0026] The average particle size of the partially lithiated silicon oxide core is 1 μm, nanosilver accounts for 0.05% of the total mass of the negative electrode material, lithium titanate accounts for 0.3% of the total mass of the negative electrode material, and carbon accounts for 0.5% of the total mass of the negative electrode material.
[0027] The preparation method of the above-mentioned high first-efficiency silicon oxide-based negative electrode material is:
[0028] S1. Add silicon dioxide particles with an average particle size of 1 μm to a stannous chloride solution with a concentration of 0.1 mol / L to obtain a mixed solution with a solid content of 20%, heat and stir the mixed solution at 30°C with a stirring speed of 100 r / min for 0.5 h to react, add a silver nitrate solution with a concentration of 0.1 mol / L after the reaction is completed, continue heating and stirring to react for 1 h, filter after the reaction is completed, and air dry at 30°C to obtain particles A;
[0029] S2, mixing the titanium source solution with particles A and polyethyleneimine to obtain a mixed solution with a solid content of 20%, wherein the molar concentration of polyethyleneimine in the mixed solution is 0.01 mol / L, and then heating and stirring the mixture at 40°C for 0.5 h. After the reaction is completed, lithium acetate is added under stirring to form a gel, and then freeze-dried to obtain powder B, wherein the titanium source solution is obtained by mixing butyl titanate with ethanol, the molar ratio of butyl titanate to lithium acetate is 1:1, and the mass ratio of lithium acetate to particles A is 1:6;
[0030] S3. Powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at 800°C for carbon coating for 1 hour to obtain a high first-efficiency silicon dioxide-based negative electrode material, wherein the gas flow rate of argon is 200 ml / min, and the gas flow rate of acetylene is 50 ml / min.
[0031] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metal lithium was used as a reference negative electrode, and a half-cell was formed with a separator and an electrolyte to perform an electrochemical performance test, with a test rate of 0.1C (first time) + 0.5C (cycle), and a charge and discharge voltage of 0.005 to 0.8 V. The discharge specific capacity of the negative electrode piece can reach 1230 mAh / g, with an initial efficiency of 83.3%, and after 20 cycles, it can still maintain 96.2% of the capacity.
[0032] Example 2
[0033] A high first-efficiency silicon oxide-based negative electrode material comprises a partially lithiated silicon oxide core, composite particles composed of nano-silver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particle, and a carbon layer coated on the surface of the lithium titanate layer.
[0034] The average particle size of the partially lithiated silicon oxide core is 5 μm, nanosilver accounts for 0.1% of the total mass of the negative electrode material, lithium titanate accounts for 1% of the total mass of the negative electrode material, and carbon accounts for 1% of the total mass of the negative electrode material.
[0035] The preparation method of the above-mentioned high first-efficiency silicon oxide-based negative electrode material is:
[0036] S1. Add silicon dioxide particles with an average particle size of 5 μm to a stannous chloride solution with a concentration of 0.3 mol / L to obtain a mixed solution with a solid content of 40%, heat and stir the mixed solution at 35°C with a stirring speed of 150 r / min for 1.5 h, add a silver nitrate solution with a concentration of 0.3 mol / L after the reaction is completed, continue heating and stirring to react for 1 h, filter after the reaction is completed, and air dry at 35°C to obtain particles A;
[0037] S2, mixing the titanium source solution with particles A and triethanolamine to obtain a mixed solution with a solid content of 25%, wherein the molar concentration of triethanolamine in the mixed solution is 0.1 mol / L, and then heating and stirring the mixture at 50°C for 0.6 h. After the reaction is completed, lithium acetate is added under stirring to form a gel, and then freeze-dried to obtain powder B; wherein the titanium source solution is obtained by mixing isopropyl titanate with ethanol, wherein the molar ratio of isopropyl titanate to lithium acetate is 1:1.5, and the mass ratio of lithium acetate to particles A is 1:10;
[0038] S3. Powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at 850°C for 2 hours to perform carbon coating to obtain a high first-efficiency silicon dioxide-based negative electrode material, wherein the gas flow rate of argon is 150 ml / min, and the gas flow rate of acetylene is 100 ml / min.
[0039] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metallic lithium was used as a reference negative electrode. A half-cell was formed with a separator and an electrolyte to test the electrochemical performance. Figure 2 , the test rate is 0.1C (first time) + 0.5C (cycle), and the charge and discharge voltage is 0.005-0.8V. The discharge capacity of the negative electrode can reach 1200mAh / g, the first efficiency is 86.6%, and after 20 cycles, it can still maintain 98.1% of the capacity.
[0040] Example 3
[0041] A high first-efficiency silicon oxide-based negative electrode material comprises a partially lithiated silicon oxide core, composite particles composed of nano-silver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particle, and a carbon layer coated on the surface of the lithium titanate layer.
[0042] Among them, the average particle size of the partially lithiated silicon oxide core is 8μm, nanosilver accounts for 0.3% of the total mass of the negative electrode material, lithium titanate accounts for 2% of the total mass of the negative electrode material, and carbon accounts for 1.5% of the total mass of the negative electrode material.
[0043] The preparation method of the above-mentioned high first-efficiency silicon oxide-based negative electrode material is:
[0044] S1. Add silicon dioxide particles with an average particle size of 8 μm to a stannous chloride solution with a concentration of 0.5 mol / L to obtain a mixed solution with a solid content of 50%, heat and stir the mixed solution at 40°C with a stirring speed of 200 r / min for 2 h, add a silver nitrate solution with a concentration of 0.5 mol / L after the reaction is completed, continue heating and stirring to react for 1.5 h, filter after the reaction is completed, and vacuum dry at 40°C to obtain particles A;
[0045] S2, mixing the titanium source solution with particles A and citric acid to obtain a mixed solution with a solid content of 35%, wherein the molar concentration of citric acid in the mixed solution is 0.6 mol / L, and then heating and stirring the mixture at 60°C for 0.7 h. After the reaction is completed, lithium acetate is added under stirring to form a gel, and then freeze-dried to obtain powder B; wherein the titanium source solution is obtained by mixing ethyl titanate with ethanol, wherein the molar ratio of ethyl titanate to lithium acetate is 1:2, and the mass ratio of lithium acetate to particles A is 1:12;
[0046] S3. Powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at 900°C for carbon coating for 2.5 hours to obtain a high first-efficiency silicon dioxide-based negative electrode material, wherein the gas flow rate of argon is 100 ml / min, and the gas flow rate of acetylene is 100 ml / min.
[0047] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metal lithium was used as a reference negative electrode. A half-cell was formed with a separator and an electrolyte to perform an electrochemical performance test. The test rate was 0.1C (first time) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The discharge specific capacity of the negative electrode piece can reach 1260mAh / g, with an initial efficiency of 85.3%. After 20 cycles, 96.5% of the capacity can still be maintained.
[0048] Example 4
[0049] A high first-efficiency silicon oxide-based negative electrode material comprises a partially lithiated silicon oxide core, composite particles composed of nano-silver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particle, and a carbon layer coated on the surface of the lithium titanate layer.
[0050] The average particle size of the partially lithiated silicon oxide core is 10 μm, nanosilver accounts for 1% of the total mass of the negative electrode material, lithium titanate accounts for 5% of the total mass of the negative electrode material, and carbon accounts for 3% of the total mass of the negative electrode material.
[0051] The preparation method of the above-mentioned high first-efficiency silicon oxide-based negative electrode material is:
[0052] S1. Add silicon dioxide particles with an average particle size of 10 μm to a stannous chloride solution with a concentration of 1 mol / L to obtain a mixed solution with a solid content of 60%, heat and stir the mixed solution at 50° C. and a stirring speed of 300 r / min for 3 h, add a silver nitrate solution with a concentration of 1 mol / L after the reaction is completed, continue heating and stirring to react for 1.5 h, filter after the reaction is completed, and vacuum dry at 100° C. to obtain particles A;
[0053] S2, mixing the titanium source solution with particles A and citric acid to obtain a mixed solution with a solid content of 40%, wherein the molar concentration of citric acid in the mixed solution is 1 mol / L, and then heating and stirring the mixture at 80°C for 1 hour. After the reaction is completed, lithium acetate is added under stirring to form a gel, and then freeze-dried to obtain powder B; wherein the titanium source solution is obtained by mixing ethyl titanate with ethanol, wherein the molar ratio of ethyl titanate to lithium acetate is 1:3, and the mass ratio of lithium acetate to particles A is 1:25;
[0054] S3. Powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at 1000°C for carbon coating for 5 hours to obtain a high first-efficiency silicon dioxide-based negative electrode material, wherein the gas flow rate of argon is 50 ml / min, and the gas flow rate of acetylene is 200 ml / min.
[0055] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metal lithium was used as a reference negative electrode. A half-cell was formed with a separator and an electrolyte to perform an electrochemical performance test. The test rate was 0.1C (first time) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The discharge specific capacity of the negative electrode piece can reach 1250mAh / g, with an initial efficiency of 80.9%. After 20 cycles, 89.7% of the capacity can still be maintained.
[0056] Comparative Example 1
[0057] Silicon oxide with an average particle size of 5 μm was placed in a vapor deposition furnace, and argon and acetylene were introduced at 850°C for carbon coating for 2 hours to obtain a silicon oxide-based negative electrode material, wherein the gas flow rate of argon was 150 ml / min, and the gas flow rate of acetylene was 100 ml / min.
[0058] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metal lithium was used as a reference negative electrode. A half-cell was formed with a separator and an electrolyte to test the electrochemical performance. The test rate was 0.1C (first time) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The discharge specific capacity of the negative electrode piece can reach 1400mAh / g, with an initial efficiency of 62.3%. After 20 cycles, the capacity retention rate was only 56.2%.
[0059] From the performance results of the materials prepared in the comparative examples, it can be seen that the present invention improves the conductivity of the material by depositing a large amount of high-conductivity nanosilver on the surface of silicon monoxide, and uses lithium titanate precursor gel to uniformly coat the silicon substrate, and adopts freeze-drying and CVD carbon coating to achieve that the lithium titanate precursor gel is originally formed into lithium-embedded zero-strain lithium titanate and uniformly coats the internal silicon substrate, thereby alleviating the volume effect of the silicon substrate material during the charge and discharge process. At the same time, excess lithium diffuses into the interior of the silicon substrate to form lithium silicate, thereby further improving the first coulomb efficiency of the material. In addition, the formation of a highly conductive carbon layer in the outermost layer not only further alleviates the volume effect of the silicon substrate material during the charge and discharge process, but also improves the conductivity of the material, reduces the specific surface area of the material, and reduces the formation of the SEI film. Therefore, the negative electrode material of the present invention has excellent cycle performance and rate performance as well as high first coulomb efficiency.
[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high first-efficiency silicon oxide-based negative electrode material, characterized in that: The negative electrode material comprises a partially lithiated silicon oxide core and composite particles composed of nanosilver coated on the surface of the core, a lithium titanate layer coated on the surface of the composite particles, and a carbon layer coated on the surface of the lithium titanate layer; In the negative electrode material, the average particle size of the silicon oxide core is 1-10 μm, nanosilver accounts for 0.05%-1% of the total mass of the negative electrode material, lithium titanate accounts for 0.3%-5% of the total mass of the negative electrode material, and carbon accounts for 0.5%-3% of the total mass of the negative electrode material; The method for preparing the high first-efficiency silicon oxide-based negative electrode material comprises the following steps: S1. Nanosilver is coated on the surface of silicon dioxide particles by chemical plating to obtain particles A. The specific steps include: adding silicon dioxide particles to stannous chloride solution to obtain a mixed solution, heating and stirring the mixed solution to react for 0.5 to 3 hours, then adding silver nitrate solution, continuing to heat and stir the mixture to react for 1 to 3 hours, filtering and drying after the reaction is completed, and obtaining the particles A. S2, mixing the titanium source solution with the particles A and the chelating agent to obtain a mixed solution, then heating and stirring to react, adding a lithium source under stirring after the reaction is completed to form a gel, and then freeze-drying to obtain a powder B; the molar ratio of the titanium source to the lithium source is 1: (1-3), and the mass ratio of the lithium source to the particles A is 1: (6-25); S3. Placing the powder B in a chemical vapor deposition furnace, and performing carbon coating by chemical vapor deposition at high temperature to obtain a high-efficiency silicon dioxide-based negative electrode material.
2. The method for preparing a high first-efficiency silicon oxide-based negative electrode material according to claim 1, characterized in that: In S1, the temperature of the heating and stirring reaction is 30~50°C, and the stirring speed is 100~300r / min; in S1, the concentration of the stannous chloride solution is 0.1~1 mol / L; in S1, the concentration of the silver nitrate solution is 0.1~1 mol / L; in S1, the solid content of the mixed solution is 20%~60%; in S1, the drying method is air drying or vacuum drying, and the drying temperature is 30~100°C.
3. The method for preparing a high first-efficiency silicon oxide-based negative electrode material according to claim 1, characterized in that: In S2, the solid content of the mixed solution is 20%~40%, and the molar concentration of the chelating agent in the mixed solution is 0.01~1 mol / L; in S2, the temperature of the heated stirring reaction is 40~80°C, and the time is 0.5~1h; in S2, the titanium source is at least one of butyl titanate, isopropyl titanate, and ethyl titanate, the lithium source is lithium acetate, and the chelating agent is at least one of polyethyleneimine, triethanolamine, and citric acid.
4. The method for preparing a high first-efficiency silicon oxide-based negative electrode material according to claim 1, characterized in that: In S3, the temperature of carbon coating by chemical vapor deposition is 800~1000℃ and the time is 1~5h.
5. The method for preparing a high first-efficiency silicon oxide-based negative electrode material according to claim 1, characterized in that: In S3, the powder B is placed in a vapor deposition furnace, and argon and acetylene are introduced at high temperature for carbon coating to obtain a high first-efficiency silicon dioxide-based negative electrode material; in S3, the gas flow rate of the argon gas is 50~200 ml / min, and the volume ratio of argon gas to acetylene is 4:1~1:
4.
6. The method for preparing a high first-efficiency silicon oxide-based negative electrode material according to claim 1, characterized in that: In S1, the average particle size of silicon oxide particles is 1 to 10 μm.
Citation Information
Patent Citations
Silicon-based anode material and preparation method and application thereof
CN105680012A
Single-layer / double-layer coated silicon oxide composite anode material and preparation method thereof
CN107959012A
Pre-lithiated silicon monoxide / carbon composite material, and preparation method and application thereof
CN112289999A
Rechargeable lithium battery including negative active material
US20120141872A1